$\mathcal{T}_{M}$-Amenability of Banach Algebras - Ali Ghaffari; Samaneh Javadi (Sahand Communications in Mathematical Analysis)
We introduce the notions of $\mathcal{T}_{M}$-amenability and $φ$-$\mathcal{T}_{M}$-amenability. Then, we characterize $φ$-$\mathcal{T}_{M}$-amenability in terms of $WAP$-diagonals and $φ$-invariant means. Some concrete cases are also discussed.